Biochemical composition of carcass, muscle and liver tissue of Labeo rohita Hamilton after feeding with sunflower (Helianthus annus) oil cake meal - Devi, Chamundeswari; Vijayaraghavan, Shantha (Indian Journal of Fisheries, 2011)
Feeding experiments were conducted on the fingerlings of Labeo rohita usingfeed containing sunflower oil cake at 20, 40 or 60% level. Wheat bran,groundnut oil cake and maize were used in the control feed. All the diets weremade isonitrogenous at 35% crude protein level and fishes were fed at therate of 3% of the body weight. At the end of six months study, highest proteinin the carcass and muscle tissue was observed at 40% inclusion of sunfloweroil cake.